Evaluation of the impact of a control program against taeniasis-cysticercosis (Taenia solium). - Aline S de Aluja; Raúl Suárez-Marín; Edda Sciutto-Conde; Julio Morales-Soto; José Juan Martínez-Maya; Nelly Villalobos (Instituto Nacional de Salud Pública, 2014)
Objetive. The impact of a control program is evaluated to eventually eradicate taeniasis-cysticercosis (Taenia solium) based on education and vaccination of pigs. Materials and methods. The prevalence of porcine cysticercosis was estimated using tongue inspection, ultrasound and determination of antibodies, before and three years after the application in three regions of the state of Guerrero. Results. A significant reduction in the prevalence of porcine cysticercosis of 7 to 0.5% and 3.6 to 0.3% estimated by tongue examination or ultrasound respectively (p menor que 0.01) and a no significant decrease in seroprevalence from 17.7 to 13.3% were observed. Conclusions. The reduction of the prevalence of taeniasis-cysticercosis establishes the program's effectiveness in preventing infection. The sustained presence of antibodies, compatible with contact of Taenia solium or other related helminths, underlines the importance of maintaining interventionsto achieve eradication.